Mermaid School - Wetzel, JoAnne; Swaney, Julianna (New York : Alfred A. Knopf, 2018)
Molly enjoys her first day at Mermaid School, where she makes new friends, learns new things, and hears a story about children with no tails.
Keywords: Stories in rhyme; First day of school -- Fiction; Schools -- Fiction; Mermaids -- Fiction; Friendship -- Fiction